Pulse article: How do you do the international standards for neurological classification of SCI anorectal exam?. (December 2017) - Alexander, Marcalee; Aslam, Hammad; Marino, Ralph
Abstract Study Design Online survey of spinal cord injury (SCI) practitioners. Objectives Determine provider understanding and routine performance of International Standards for Neurologic Classification of Spinal Cord Injury (ISNCSCI) anorectal examination. Setting International online questionnaire. Methods A descriptive survey was developed to assess current performance of the ISNCSCI anorectal exam. Information about this survey was disseminated through social email and international societies between the months of March and April 2017. Results Two hundred and fifteen SCI practitioners completed the survey. Of these, 157 (73%) were specialists in physical medicine and rehabilitation, 32 (15%) were physical therapists, 6 were neurologists, 6 were orthopedists, and 3 were neurosurgeons. Of responders, 90% routinely personally performed the anal exam of the ISNCSCI, of whom, 42 placed firm pressure against the anal sphincter, 58 placed firm pressure against the rectal wall, and 87 placed firm pressure against the anal sphincter and rectal wall as part of the exam. On a routine basis, 74% tested sensation at the junction of the anal sphincter and skin, 82% had the patient attempt to squeeze their finger, and 50% performed the bulbocavernosus reflex. Conclusions Marked inconsistency exists in the performance of the ISNCSCI anal examination. Researchers and clinicians need more education about the performance of the examination. Consideration should be given for the components of deep rectal sensation and anal pressure to be separately documented in the neurologic exam and for researchers to focus separately on recovery of sacral function vs. ambulatory function in clinical trials.